Concerning the Ethical Shores and Talismans of Modern Social-political Reality of Ukraine - Samchuk, Zoreslav (Filosofiya osvity. Philosophy of Education, 2006)
The essential feature of social-political reality of modern Ukraine is a state of bordering the essence of which is that world outlook and economically our country completed the cycle of primary state development. That is why now we are facing the necessity first — complex rethinking of passed way and secondly — conceptualization of future development. If the previous phase of formation has been manifesting importance of economic and material-technical aspects of social activity (by the way, it has not succeeded), on the other hand the future very often is associated with spiritual existence, emphasizing on the necessity of spreading ethics in all spheres of social life as a needed condition of consolidating and maximum dynamic development of Ukraine.